Achieving Manufacturing Excellence Using Lean DMAIC - Rindi Kusumawardani; Ana; Moses Laksono Singgih (Engineering Proceedings)
This paper explores the role of business process optimization in achieving manufacturing excellence in railway manufacturing through Lean principles and Quality Function Deployment (QFD). It identifies key inefficiencies, such as waiting times, overproduction, and document errors, using the DMAIC method, along with Root Cause Analysis (RCA) and Failure Mode and Effect Analysis (FMEA), to prioritize waste reduction. A significant 42.86% of activities were classified as non-value added, pointing to substantial opportunities for improvement. This study proposes key solutions, including the development of a shared database, streamlined procedures, and the alignment of targets with the Master Production Schedule to reduce waste and improve operational efficiency. These recommendations aim to foster manufacturing excellence by enhancing communication, process integration, and employee training.